PENGEMBANGAN MEDIA PEMBELAJARAN BERUPA VIDEO ANIMASI SEBAGAI MEDIA PEMBELAJARAN INOVATIF DI SEKOLAH DASAR - Yulia, Raida (Jurnal Teladan: Jurnal Ilmu Pendidikan dan Pembelajaran, 2022)
The background of the problem in this study is the low motivation of students to learn which also affects the low student learning outcomes. The use of appropriate media in learning will increase students' learning motivation and create fun in learning activities. In increasing the motivation of a student, it must first create fun in learning, where in creating student fun is by using interactive media in learning, one of which is animated video media. The method used by the author in this study is the research and development method or commonly referred to as the R&D method, which is the method used to develop a product. Thus, the implementation of this research can achieve the research objectives, namely developing animated video learning media products as innovative learning media that are suitable for use in learning for third grade elementary school students. The results showed that the animated video learning media that was developed was declared very feasible to use. Teacher validation showed an average score of 90% in the very appropriate category, and the third grade elementary school student trial showed an average score of 94.5% in the very feasible category. Based on the value obtained, the learning media in the form of animated videos as innovative learning media is appropriate for use in third grade elementary school students and provides changes to increase student motivation.